The nude : a novel - Lindley, C. Michelle (Atria Books, 2024)
"Art historian, Elizabeth Clarke, is sent to a remote island in Southern Greece to acquire a rare female nude sculpture for a Los Angeles collection. Disoriented by time zones, migraines, and suspicious details surrounding the figure's discovery, she's dependent on her flirtatious but guileless translator. The last thing she expects is to be so pulled to his wife, Theo, a subversive artist who has amassed a small following for her provocative self-portraits, which seek to deconstruct the objectification of the female form. As Elizabeth immerses herself in the island's cobblestoned mazes and sumptuous cuisine, and falls deeper into an infatuation with Theo -- and Theo's art -- she starts to question her role in the acquisition of cultural artifacts. And when, after a hazy night out, both Elizabeth and the nude are violated in divergent but damaging ways, Elizabeth begins to see a parrallel between the sculpture and herself. What does it mean for a woman to navigate morally complicated negotiations of property in a male-directed world? What other kinds of ownership -- or self-ownership -- might be possible?"--